THE ROLE OF LANGUAGE IN SHAPING HISTORICAL NARRATIVES - Abdumutalibova Mohlaroyim Xabibullo qizi The student of Chirchik State Pedagogical University Scientific advisor: Khamitov Eldorbek Erkin o’g’li (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Language is not only a means of communication, it is a vehicle for cultural memory, identity, and historical interpretation. It examines the effect of language on shaping and sustaining historical narratives as it relates to the way in which it frames orientation, privilege and marginal insinuation. Through an analysis of linguistic choices, metaphors, translation practices, and shifts in terminology, the study demonstrates the subjectivity that is enshrined in the accounts that go on to form the basis for history. This research aims to deepen our understanding of how language functions not just as a record of history but as a tool for shaping collective memory. A review of case studies demonstrates the dynamic interaction between linguistic framing and historical interpretation, emphasizing the need for critical engagement with language in historical discourse. Keywords: Language, Historical Narratives, Collective Memory, Linguistic Framing, Historiography